Local higher integrability for unsteady motion equations of generalized Newtonian fluids. (November 2020) - Sin, Cholmin
Abstract: In this paper, we show local higher integrability of the gradient of weak solutions for unsteady motions of generalized Newtonian fluids including electrorheological fluids under the restriction p ( z ) ≥ 3 n + 2 n + 2 . Moreover, this is a new result even for corresponding Stokes setting or a system with p -structure depending on the symmetric gradient under the restriction p ( z ) > 2 n n + 2 .